Econometric theory and practice : frontiers of analysis and applied research - Phillips, P. C. B.; Corbae, Dean.; Durlauf, Steven N.; Hansen, Bruce E., 1962- (Cambridge ; New York : Cambridge University Press, 2006)
This book is a collection of essays written in honour of Professor Peter C.B. Phillips of Yale University by some of his former students. The essays analyze several state-of-the-art issues in econometrics, all of which Professor Phillips has directly influenced through his seminal scholarly contribution and remarkable achievements as a teacher.
A collection of essays written in honor of Prof. Peter C.B. Phillips of Yale University.
Includes bibliographical references and index.
rua 31/10/13
Loans
Keywords: Econometrics